(untitled) - Denicolo, Pam (London, 2018)
Do you want to thrive in your doctoral research? Do you want to do more than just survive? If so this is the book for you.Focused on empowering the doctoral researcher, it is packed with advice on how to make the best of opportunities and enjoy your research experience while dealing with challenges. Whether you need to find sources of constructive feedback, are facing an unexpected disturbance to your project, or have ambitions beyond your academic goals, this book provides practical, flexible tips for conducting effective research and engaging with the complex world of academia, including how to:Maintain momentum through each stage of the research process, Make the most of available resources, training, and support, Explore new technologies, networks, and dissemination strategies, Maximize the value of assessment, Use this project as a springboard into further research and career opportunities. Acknowledging that every doctoral experience is unique, this book goes beyond a script for success and instead offers a full studio of flexible, creative tools and adaptable action points that equip you to compose your own distinctive story of research success
Keywords: Nghiên cứu,Học viên tiến sĩ,Doctoral students,Research; Sổ tay, sách hướng dẫn, v.v.,Handbooks, manuals, etc